Copper‐Photocatalyzed Hydroboration of Alkynes and Alkenes. (17th May 2021) - Zhong, Mingbing; Gagné, Yohann; Hope, Taylor O.; Pannecoucke, Xavier; Frenette, Mathieu; Jubault, Philippe; Poisson, Thomas
Abstract: The photocatalytic hydroboration of alkenes and alkynes is reported. The use of newly‐designed copper photocatalysts with B2 Pin2 permits the formation a boryl radical, which is used for hydroboration of a large panel of alkenes and alkynes. The hydroborated products were isolated in high yields, with excellent diastereoselectivities and a high functional group tolerance under mild conditions. The hydroboration reactions were developed under continuous flow conditions to demonstrate their synthetic utility. The reaction mechanism was studied and suggested an oxidation reaction between an in situ formed borate and the Cu‐photocatalyst in its excited state for the boryl radical formation. Abstract : We report herein the photocatalytic hydroboration of alkenes and alkynes using newly‐designed copper photocatalysts with B2 Pin2 . The hydroborated products were obtained under mild conditions in high yields, excellent diastereoselectivities, a high functional group tolerance and developed under continuous flow conditions to demonstrate their synthetic utility. Finally, the reaction mechanism was also studied.